Tirofiban Induced Thrombocytopenia: A Rare but Severe Adverse Effect - Muhammad Shabbir Rawala; Amna Saleem Ahmed; Kanna Posina; Varun Sundaram (Greater Baltimore Medical Center, 2020)
With the advent of medical technology, coronary angiography is a common practice to evaluate patient for coronary artery disease. Normally, patients undergoing angiogram receive antiplatelets, anticoagulants, and platelet aggregation inhibitor agents. Glycoprotein IIb/IIIa receptor inhibitors are a type of platelets antiaggregant agents that can cause severe thrombocytopenia in very few cases. We present a case of a 69-year-old female who presented with chest pain, underwent an angiography and had two stents placed. She was administered tirofiban during angiogram that caused acute severe thrombocytopenia decreasing her platelets count from 224 to 2 k/mm3 within 1 day. Patients platelets gradually recovered after trial of steroid and platelets transfusion. Antiplatelets (Aspirin and Clopidogrel) were resumed; however, patient's platelets remained stable.